2012
DOI: 10.1371/journal.ppat.1002868
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-alpha Subtype 11 Activates NK Cells and Enables Control of Retroviral Infection

Abstract: The innate immune response mediated by cells such as natural killer (NK) cells is critical for the rapid containment of virus replication and spread during acute infection. Here, we show that subtype 11 of the type I interferon (IFN) family greatly potentiates the antiviral activity of NK cells during retroviral infection. Treatment of mice with IFN-α11 during Friend retrovirus infection (FV) significantly reduced viral loads and resulted in long-term protection from virus-induced leukemia. The effect of IFN-α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 67 publications
6
63
0
Order By: Relevance
“…In the current study, IFN-␣14 treatment induced expression of the cytotoxic molecule TRAIL on NK cells, which has been associated with the control of HCV in patients treated with pegylated IFN-␣2 and ribavirin (65). In addition, IFN-␣-induced NK cell activation and increased TRAIL expression correlated with retroviral control in a mouse model (8), and NK cell responses have been shown to play an important role in HIV-1 immunity (66). APOBEC3G is an intrinsic HIV restriction factor (67,68), which upon incorporation into newly assembled virions restricts HIV-1 replication in the next target cell by physically impeding reverse transcription and/or inducing lethal G-to-A hypermutations (68-72), primarily converting tryptophans (TGG) to stop codons (TGA).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In the current study, IFN-␣14 treatment induced expression of the cytotoxic molecule TRAIL on NK cells, which has been associated with the control of HCV in patients treated with pegylated IFN-␣2 and ribavirin (65). In addition, IFN-␣-induced NK cell activation and increased TRAIL expression correlated with retroviral control in a mouse model (8), and NK cell responses have been shown to play an important role in HIV-1 immunity (66). APOBEC3G is an intrinsic HIV restriction factor (67,68), which upon incorporation into newly assembled virions restricts HIV-1 replication in the next target cell by physically impeding reverse transcription and/or inducing lethal G-to-A hypermutations (68-72), primarily converting tryptophans (TGG) to stop codons (TGA).…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, evolutionary selection of multiple functional IFN-␣ subtypes indicates that each subtype has essential and nonredundant functions (6). Evidence of this includes studies in the Friend retrovirus (FV) model, which showed that treatment with distinct IFN-␣ subtypes induced specific downstream responses that effectively controlled FV infections, whereas other subtypes induced responses that were ineffective (7,8). Furthermore, murine herpesvirus or influenza virus infections were controlled by different subtypes than those inhibiting FV (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies demonstrated that IFN-a1, IFN-a4, IFN-a5, IFN-a6 and IFN-a9 mediate anti-viral activity against herpes simplex virus (Harle et al, 2002), whereas IFN-a11 and IFN-a4 were the best candidates in blocking the replication of mengovirus (van Pesch et al, 2004). In vivo, it was shown that during Friend retrovirus (FV) infection of mice, therapeutic treatment with IFN-a1, IFN-a4, IFN-a9 and IFN-a11 reduced the viral loads significantly, whereas IFN-a2, IFN-a5 and IFN-a6 could not inhibit viral replication (Gerlach et al, 2009;Gibbert et al, 2012). In DNA-vaccination studies with different IFN-a subtypes against murine cytomegalovirus (MCMV) infection, it was shown that vaccination with IFN-a1, IFN-a4 and IFN-a9 as adjuvants resulted in decreased viral loads after virus challenge in the muscle only, whereas vaccination with IFN-a6 inhibited MCMV replication in all the organs investigated.…”
Section: Ifn-a Subtypesmentioning
confidence: 99%
“…We investigated the immunomodulatory effects of some IFN-a subtypes during Friend Retrovirus infection in vivo. IFN-a1 stimulated virus-specific cytotoxic T cells, and during treatment with IFN-a11 or IFNa1, both are required for an optimal NK cell response (Gerlach et al, 2009;Gibbert et al, 2012). Others investigated the immunomodulatory effect of IFN-a2 on NK cells during treatment of HCV-infected patients (Ahlenstiel et al, 2011).…”
Section: Ifn-a Subtypesmentioning
confidence: 99%